1977
DOI: 10.2466/pms.1977.44.3c.1179
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Summation Effects on Lingual Vibrotactile Thresholds

Abstract: Ascending lingual vibrotactile thresholds at 250 Hz were obtained for four groups of normal-speaking adult subjects. Contactor areas were varied for each respective group. Threshold values in microns plotted as a function of the area of vibratory displacement indicated a spatial summation function for the larger contactors (greater than .02 cm2). Findings are discussed in terms of the nature of lingual-tactile mechanoreception and possible implications for neural control mechanisms subserving speech production. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0

Year Published

1979
1979
1987
1987

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…The contactor in the vibratory system employed by Geldard and Sherrick (1971) was even larger than that of Gescheider (1966Gescheider ( , 1967, a fact that, along with the forced-choice methodology, caused the fusion thresholds to be even lower. The fact that the fusion thresholds from the present study were twice as large as those reported by earlier investigators adds support to the observation that the peripheral and central neural mechanisms of the cutaneous system have sufficient specificity to make spatial (contactor-size) as well as temporal discriminations (Telage & Warren, 1977;Verrillo, 1966;Verrillo & Chamberlain, 1972).…”
Section: Resultssupporting
confidence: 89%
“…The contactor in the vibratory system employed by Geldard and Sherrick (1971) was even larger than that of Gescheider (1966Gescheider ( , 1967, a fact that, along with the forced-choice methodology, caused the fusion thresholds to be even lower. The fact that the fusion thresholds from the present study were twice as large as those reported by earlier investigators adds support to the observation that the peripheral and central neural mechanisms of the cutaneous system have sufficient specificity to make spatial (contactor-size) as well as temporal discriminations (Telage & Warren, 1977;Verrillo, 1966;Verrillo & Chamberlain, 1972).…”
Section: Resultssupporting
confidence: 89%
“…The purpose of the present investigation was to provide further explanation of the frequency effect on subjective suprathreshold vibrotactile magnitude functions by obtaining power function curves at different frequencies from the human tongue. Exploration of the human tongue has been shown to be helpful in understanding the effect of frequency on vibrotactile threshold responses of cutaneous mechanoreceptors (Telage & Warren, 1977;Verrillo, 1966).…”
mentioning
confidence: 99%
“…This discrepancy might be explained by the difference in neural receptor populations resulting from clamping the tongue. It has previously been shown that the receptors on the lingual dorsal surface differ from the more ventrally located Pacinian corpuscles in such response characteristics as frequency-sensitivity (Telage & Petrosino , 1978) and spatial summation (Telage& Warren, 1977). Additionally , clamping the tongue tends to push the Pacinian receptors toward the surface, where they may be more easily excited by vibratory stimulation .…”
Section: Resultsmentioning
confidence: 99%